Exploring Strategies For Expanding The Xiaohongshu App In Malaysia And Singapore: A Study On Developing Chinese Social Media Overseas - Ying, Yin; Xiangyang, Liu; Xuerong, Bao (STIE Malangkucecwara, 2024)
This article discusses China's unique social media landscape, which is shaped by the country's culture, politics, and regulatory environment. Chinese social media platforms like WeChat, Weibo, and Xiaohongshu are deeply integrated and innovative, with features such as virtual red envelopes and mini-programs that significantly boost user engagement.However, expanding these platforms overseas presents challenges, such as cultural differences, regulatory environment, and competition. The article focuses on the case of Xiaohongshu (RED). It proposes strategies to improve customer loyalty and functionality in the context of e-commerce, utilizing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) as the theoretical framework.The article highlights the importance of understanding the cultural norms and preferences of the target audience, complying with local laws and regulations, and finding ways to differentiate Chinese social media platforms from established players in the market.